The influence of entrepreneurial culture, management support and work discretion on innovation: examining the conditional role of organizational tolerance and positional-level - Michael Msawenkosi Thabethe; Abdela Kosa Chebo; Shepherd Dhliwayo (Cogent Business & Management, 2024)
The purpose of this study was to investigate the numerous ways that entrepreneurship culture (EC) influences innovativeness. The conditional effect of EC on innovativeness is further examined in light of the various organizational tolerance levels and positioning levels. Data were gathered from 647 respondents chosen from the KZN Department of Education and quantitatively analysed using SEM conditional analysis and descriptive statistics. The results of the study demonstrate that EC has a substantial direct effect on innovativeness, but that it has no significant indirect effect through managerial support or work discretion. However, there is a conditional significant mediation with organizational tolerance even though there is no indirect influence of EC on innovativeness through work discretion. Therefore, it is advised that the administration of the Department of Education be expected to provide employees more flexibility and accept their (employees) mistakes in order to encourage them to work independently toward innovation.
Keywords: 650; entrepreneurial culture; innovativeness; management support; work discretion; organizational tolerance; positional level; conditional effect; SEM; department of education